La discriminación y exclusión de los profesionales a las fuentes de trabajo incide en su desarrollo profesional y vulneración del derecho al trabajo - María del Cisne, Cambizaca Mora. (2016)
This research is framed within the parameters established by the National University of Loja, the title is "DISCRIMINATION AND EXCLUSION OF PROFESSIONAL SOURCES OF WORK SHINES IN YOUR DESARROLLOPROFESIONAL AND VIOLATIONS OF THE RIGHT TO WORK" whose overall objective, a study, conceptual, legal, doctrinal and critical about discrimination and exclusion of professionals, professional development impacts. In order to achieve this objective make use of various scientific methods used in the research process, such as: scientific, historical, analytical, inductive, deductive, synthetic, etc., so it also applies survey of 30 public servants both public and private entities and interview five legal professionals; of those who got excellent results like that if there is discrimination and exclusion of professionals in the workplace and violation of the right to work, so that a reform of this fact is necessary. Fieldwork and this thesis, let me get grounded, clear and precise criteria, very important literature contributed to the verification of objectives and rationale of the proposal to contribute to the changes made. After analyzing all the results, it was deduced, conclusions and recommendations, to finally raise a reform proposal with which I intend to solve the problem.